Building a Sustainable School Reputation through Quality Management, A Study at SMP Negeri 7 Yogyakarta - Sapto Pamungkas; Diana Leli Indratno; Heru Kuncorowati (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
School reputation is a strategic asset in the modern education ecosystem in the information age. Schools with a good reputation will attract quality inputs (students, teachers, resources) to be processed into high-quality outputs in a continuous quality management cycle. This study aims to analyze the influence of quality management, consisting of the following elements: quality of the learning process, teacher competence, quality of administrative services, and good governance, on the formation of school reputation. The study was conducted using a quantitative approach through an online survey of 100 respondents, including teachers, staff, parents, and students at a high school in Yogyakarta City. The sample was taken purposively. Multiple linear regression statistical analysis was used for data analysis. The results of this study found a positive influence of quality management, reviewed in the elements of the learning process, teacher competence, quality of administrative services, and good governance, on school reputation. The results of this study provide insight for practitioners and academics in developing a sustainable school reputation through school quality management.